Intra-annual Runoff Distribution in the Pripyat River Basin - Volchak Alexander; Parfomuk Sergey; Sidak Svetlana (E3S Web of Conferences, 2020)
The time variability features of the intra-annual runoff distribution in the Pripyat River basin at the present stage are considered. The study used data from 10 active gauging-stations at the basin area for the period of enabled observations. Changes in the nature of natural runoff regulation of rivers are shown. An increase in the coefficient of natural runoff regulation after the period 1970-1983 for the rivers of the Pripyat River basin was revealed. The relationship between the coefficient of uneven runoff and the share of spring flood was established.